Renal artery thrombosis in SARS-CoV-2 infection: a case report - Huayan Huang; Chunguang Lin; Yongdong Chen; Xiuting Wu; Miaomiao Lin; Siqi Chen; Kai Li (BMC Nephrology, 2022)
Abstract Background Coronavirus disease 2019 (COVID-19) is identified as the pneumonia and acute respiratory distress syndrome caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). The intravascular thrombotic phenomena related to the COVID-19 are emerging as an important complication that contribute to significant mortality. Case presentation We present a 62-year-old man with severe COVID-19 and type 2 diabetes. After symptomatic and supportive treatment, the respiratory function was gradually improved. However, the patient suddenly developed abdominal pain, and the enhanced CT scan revealed renal artery thrombosis. Given the risk of surgery and the duration of the disease, clopidogrel and heparin sodium were included in the subsequent treatment. The patient recovered and remained stable upon follow-up. Conclusions Thrombosis is at a high risk in patients with severe COVID-19 pneumonia because of hypercoagulable state, blood stasis and endothelial injury. Thrombotic events caused by hypercoagulation status secondary to vascular endothelial injury deserves our attention. Because timely anticoagulation can reduce the risk of early complications, as illustrated in this case report.